Isolation and characterization of compounds from the stem bark of Uvaria rufa (Annonaceae)= (Pemisahan dan Pencirian Sebatian dari Kulit Batang Uvaria rufa (Annonaceae)) - Rosandy, Andi Rifki; Din, Laily; Yaacob, W. A.; Nik Yusoff, Nik Mohd. Idris; Sahidin, I.; Latip, Jalifah; Nataqain, Syarul; Mohd Noor, Normah (Universiti Kebangsaan Malaysia (UKM), 2013)
Isolation of compounds from methanol extract of the stem bark of Uvaria rufa has been conducted by using radial chromatography. Their structures were elucidated by UV, IR, NMR and mass spectroscopy, and by comparison with the literature. Seven compounds were isolated namely benzyl benzoate (1), caryophyllene oxide (2), glutinol (3), 5-hydroxy-7-methoxyflavone (4), 5-hydroxy-6,7-dimethoxyflavone (5), 2,5-dihydroxy-7-methoxyflavanone (6)and 5,7-dihydroxyflavanone (7). Separation of the caryophyllene oxide (2), glutinol (3) and 5,7-dihydroxyflavanone from Uvaria rufa has never been reported.